Genomic determination of CR1 CD35 density polymorphism on erythrocytes of patients with gallbladder carcinoma - Jiao, Xing-Yuan (World J Gastroenterol, 2004)
AIM: To study the changes of quantitative expression, adhering activity and genomic density polymorphism of complement types in erythrocytes (CR1) of patients with gallbladder carcinoma and the related clinical significance. METHODS: Polymerase chain reaction (PCR), Hind III restriction enzyme digestion, quantitative assay of CR1 and adhering activity assay of CR1 in erythrocytes were used. RESULTS: The number and adhering activity of CR1 in patients with gallbladder carcinoma (0.738 ± 0.23, 45.9 ± 5.7) were significantly lower than those in chronic cholecystitis and cholecystolithiasis (1.078 ± 0.21, 55.1 ± 5.9) and healthy controls (1.252 ± 0.31, 64.2 ± 7.4) (P < 0.01). The number and adhering activity of CR1 in patients with chronic cholecystitis and cholecystolithiasis (1.078 ± 0.21, 55.1 ± 5.9) were significantly lower than those in healthy controls (1.252 ± 0.31, 64.2 ± 7.4) (P < 0.05). There was a positive correlation between quantitative expression and adhering activity of CR1 (r = 0.79, P < 0.01). Compared with those on preoperative day (0.738 ± 0.23, 45.4 ± 4.9), the number and adhering activity of CR1 in patients with gallbladder carcinoma decreased greatly on the third postoperative day (0.310 ± 0.25, 31.8 ± 5.1) (P < 0.01), and on the first postoperative week (0.480 ± 0.25, 38.9 ± 5.2) (P < 0.01), but they were increased slightly than those on the preoperative day (P > 0.05). The number and adhering activity of CR1 recovered in the second postoperative week (0.740 ± 0.24, 46.8 ± 5.9) (P < 0.01) and increased greatly in the third postoperative week (0.858 ± 0.35, 52.7 ± 5.8) (P < 0.01) in comparison with those on the preoperative day and in the first postoperative week. The number and adhering activity of CR1 of gallbladder carcinoma patients with infiltrating, adjacent lymphogenous and distant organ metastases were significantly lower than those of gallbladder carcinoma patients without them (P < 0.01). No difference was observed between the patients with gallbladder carcinoma and healthy individuals in the spot mutation rate of CR1 density gene (χ (2) = 0.521, P > 0.05). The distribution of expression was 67.8% in high expression genomic type, 24.8% in moderate expression genomic type, and 7.4% in low expression genomic type. The number and adhering activity of CR1 high expression genomic type gallbladder carcinomas (0.749 ± 0.22, 42.1 ± 6.2) were significantly lower than those of healthy individuals(1.240 ± 0. 29, 63.9 ± 7.2), and were also significantly lower than those of healthy individuals (0.921 ± 0.23, 54.8 ± 7.1), but no difference was observed between the number and adhering activity of CR1 lower expression genomic type gallbladder carcinomas (0.582 ± 0.18, 44.3 ± 5.5) and those of healthy individuals (0.610 ± 0.20, 45.8 ± 5.7) (P > 0.05). CONCLUSION: Defective expression of CR1 in gallbladder carcinoma is mostly acquired through central peripheral mechanisms. The changes in CR1 quantitative expression and adhering activity are consanguineously related to the development and metastasis in gallbladder carcinoma.